MENINGKATKAN KETERAMPILAN BERPIKIR TINGKAT TINGGI SISWA KELAS XI MELALUI PEMBELAJARAN MATEMATIKA BERBASIS PROBLEM BASED LEARNING PADA MATERI TRIGONOMETRI - Ofir Hawila Bantaika; Samijo Samijo; Dian Devita Yohanie (UPT Penerbitan Universitas Jember, 2022)
The purpose of this study was tooderermine (1) teacher activities innproblem based learning on trigonometric comparison material. (2) Student activities in problem-based learning on trigonometric comparison material. (3) Improvement of high-order thinking skills of class XI students on trigonometric comparison materials through problem-based learning mathematics. This study usess quantitative approach, the research design iss one group pretest-posttest design. Theepopulations and sample are alls class XI SMK PGRI 3 as many as 21 students. Thee sampling techniquee iss simple random sampling. Data analysis used t-test analysis. Based on the results the study, it was concluded thats: (1) Teacher activity in problem-based learning on trigonometric comparison material, in good category with an activity score of 75. (2) Student activity in problem-based learning on trigonometric comparison material, very category good with an activity score of 87.5. (3) There is ann increase in high-order thinking skill off class XI students in trigonometric comparisons through problem-based learning mathematics. This can be proven from t-count 10,542 t-table 2,086 with sig. (2-tailed) att aa significant level off , soo thats H0. is rejected and Ha. is accepted with thee result that thee pretest score of 58.67 increases in theeposttest value of 79.3. Keywords: Higher Order Thinking Skills, Trigonometry,.Problem-Based Learning